Green tea extract-mediated augmentation of imipenem antibacterial activity against Enterobacter cloacae clinical isolates - Rezky Yanuarti; Firzan Nainu; Sartini Sartini (Universitas Ahmad Dahlan, 2021)
The emergence of pathogenic bacteria with Î²-lactam antibiotics-resistant profile has threatened the continued use of such antibiotics in the future. This research was conducted to investigate the antimicrobial activity of green tea ethanol extract (GTE) and its ability to improve the antibacterial action of several Î²-lactam antibiotics against Enterobacter cloacae clinical isolates. The simplicia of green tea was extracted by sonication for 30 minutes using 50% ethanol solvent, and the total phenolic content of the GTE was subsequently determined. Next, the GTE used in testing against two clinical isolates of E. cloacae was obtained from the Pathology Laboratory of Wahidin Sudiro Husodo Hospital in Makassar. The sensitivity of bacteria to GTE was confirmed using the agar diffusion method, the VitekÂ® rapid method, and the double-disk synergistic test. Antibacterial activity of antibiotics, GTE, and combination of antibiotics with GTE were then tested against clinical isolates of E. cloacae using the checkerboard microdilution assay. The results showed that GTE contained 51.64 Â± 0.21 % measured as gallic acid equivalent and 37.95 + 5.17 % Epigallocatechin gallate (EGCG). The confirmatory test results indicated that one clinical isolate of E. cloacae (code 13/04) was resistant to amoxicillin-clavulanate but did not produce an extended-spectrum Î²-lactamase (ESBL). Another clinical E. cloacae isolate (code 275B/06) was indicated to produce ESBL and demonstrated to yield resistance to amoxicillin-clavulanate and cefotaxime. The minimum inhibitory concentration of GTE against the two clinical isolates of E. cloacae was >8000 ppm (8 mg/ml). In conclusion, GTE could not increase the antibacterial activity of amoxicillin and cefotaxime, but it was sufficient to improve the activity of imipenem against the tested isolates of E. cloacae.